Control of anxiety through music in a head and neckoutpatient clinic: a randomized clinical trial - Mariana Alves Firmeza; Andrea Bezerra Rodrigues; Geórgia Alcântara Alencar Melo; Maria Isis Freire de Aguiar; Gilmara Holanda da Cunha; Patrícia Peres de Oliveira; Alex Sandro de Moura Grangeiro
Abstract OBJECTIVE Evaluating the effectiveness of a musical intervention in reducing anxiety and vital parameters in people suffering from head and neck cancer. METHOD A randomized controlled clinical trial, performed in a head and neck outpatient clinic with 40 participants, subdivided into two groups (intervention and control).The classicalmusic"Spring" from The Four Seasons by Vivaldi was used as an intervention.The State-Trait Anxiety Inventory (STAI) was used as the data collectioninstrument,along with an inventory of socio-demographic and clinical data. Student'st-test was used to verify intragroup and intergroup statistical significance. RESULTS Participants presented a statistically significant reduction in levels of perceived anxiety (t= 12.68; p<0.001),as well as blood pressure levels (t = 4.56; p<0.001); pulse (t = 6.15; p<0.001) and respiratory rate (t = 5.10; p<0.001). CONCLUSION Music has proven to be an effective non-pharmacological therapeutic resource in managinganxiety in an outpatient setting for people with cancer, as well as in reducing blood pressure, pulse and respiratory rate. Brazilian Registry of Clinical Trials: RBR-7W4YJJ